PRINSIP PENATAAN ARSITEKTUR KORIDOR JALAN ALMUSLIM PEUSANGAN BIREUEN - Aris Munandar; Istiqamah (Jurnal Kreatif : Desain Produk Industri dan Arsitektur, 2023)
The condition of Almuslim road corridor is seen from the aspect of accessibility, there is congestion on weekdays and working hours, this is due to parking vehicles on the road, because the local government has not planned a special parking area. The problem that occurs in the city of Matangglumpangdua is a guide to the design of the Almuslim corridor arrangement which is not implemented properly so that there is discomfort for the city community in activities. This research is expected to provide an alternative reference guide for the design of the Almuslim Street corridor in the city of Matangglumpangdua, especially for the community and the Government can be useful for the development of science and knowledge of urban architecture so that it can add insight into the principles of urban planning and design. Realize human comfort There are four solutions on the principle of structuring guidelines for the arrangement of the corridor arrangement of Jalan Almuslim kota matangglumpangdua, namely the arrangement of circulation and parking, signage system, pedestrian ways and building arrangements. The visual pollution that the signage produces needs to be arranged so that there will be a irregular. Developing land functions or unbuilt areas as parking areas vehicles area, so that there is no congestion.